2:15 hope it helps your welcome
Answer:
The inverse for log₂(x) + 2 is - log₂x + 2.
Step-by-step explanation:
Given that
f(x) = log₂(x) + 2
Now to find the inverse of any function we put we replace x by 1/x.
f(x) = log₂(x) + 2
f(1/x) =g(x)= log₂(1/x) + 2
As we know that
log₂(a/b) = log₂a - log₂b
g(x) = log₂1 - log₂x + 2
We know that log₂1 = 0
g(x) = 0 - log₂x + 2
g(x) = - log₂x + 2
So the inverse for log₂(x) + 2 is - log₂x + 2.
123 - Use PEMDAS but since you have both division and multiplication you can just go from left to right
Answer:
Image isn't popping up
Step-by-step explanation:
Answer:
7:21
Step-by-step explanation:
Lcm(9,12)=9*4=36 minutes later
That is
6:45+36min=7:21